Pregnancy Disorders and Access to Female Workers’ Health Services in Sidoarjo Industrial Area During Covid-19 Pandemic - Indriati Paskarini; Tri Martiana; Firman Suryadi Rahman; Putri Ayuni Alayyannur; Shintia Yunita Arini (Institute of Medico-legal Publications Pvt Ltd, 2021)
Maternal health is part of public health that will show a positive trend if there is a decrease in maternalmortality and an increase in delivery assistance provided by health workers in health service facilities.to know the relationship between pregnancy disorders and access to health services for female workersin the industrial area of Sidoarjo. this research was cross-sectional The sample of this study was 159midwives. ANC visits of female workers are still low and have not reached 90%. Many female workershave experienced various pregnancy disorders. These pregnancy disorders include; abortion, anemia, andHyperemesis GravidarumThe biggest obstacle to antenatal care performed by female workers is time andcost. During the Covid-19 pandemic, antenatal care services have made adaptations by implementing theCOVID-19 health protocol.